1992
DOI: 10.1161/01.atv.12.11.1274
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic ACAT activity in African green monkeys is highly correlated to plasma LDL cholesteryl ester enrichment and coronary artery atherosclerosis.

Abstract: Previous studies and this study of African green monkeys show a strong positive correlation between plasma low density lipoprotein (LDL) size and the extent of coronary artery atherosclerosis (CAA). Increased LDL size was principally due to the accumulation of cholesteryl oleate molecules within the particle core, suggesting that many of these cholesteryl esters were of tissue origin, i.e., from the acyl-coenzyme A: cholesterol acyltransferase (ACAT) reaction instead of the lecithin: cholesterol acyltransferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 38 publications
5
81
0
2
Order By: Relevance
“…20 These dietary polyunsaturated fatrelated changes in the risk profiles of young animals were consistent overall with a decreased risk for atherosclerotic CHD because they mirrored those in adult animals fed these same diets in which less atherosclerosis was found. 48 When atherosclerosis evaluations were made in the young animals of this study, less extensive and severe coronary artery atherosclerosis was found in the animals fed polyunsaturated fat. 49 Therefore, the results in this primate model show a benefit of early intervention with dietary polyunsaturated fat against coronary artery atherosclerosis development.…”
Section: Discussionmentioning
confidence: 72%
“…20 These dietary polyunsaturated fatrelated changes in the risk profiles of young animals were consistent overall with a decreased risk for atherosclerotic CHD because they mirrored those in adult animals fed these same diets in which less atherosclerosis was found. 48 When atherosclerosis evaluations were made in the young animals of this study, less extensive and severe coronary artery atherosclerosis was found in the animals fed polyunsaturated fat. 49 Therefore, the results in this primate model show a benefit of early intervention with dietary polyunsaturated fat against coronary artery atherosclerosis development.…”
Section: Discussionmentioning
confidence: 72%
“…36 The stimulation of hepatic cholesteryl ester secretion was apparently due to a stimulation of hepatic acyl coenzyme A:cholesterol acyltransferase by oleic acid. 37,38 In the mice of these studies, enrichment of LDL with cholesteryl oleate was most pronounced in the cis mono and sat groups, although the lipid milieu in the core of the LDL particles of these mice was quite different from that found in monkeys and humans. A high percentage of triacylglycerol was found in the mouse LDL (Table 4), and significant quantities of cholesteryl arachidonate (and n-3 fatty acid cholesteryl esters in the n-3 poly group) were also found (Table 5).…”
Section: Discussionmentioning
confidence: 79%
“…The predominant mammalian hepatic sterol ester which reflects ACAT activity is cholesteryl oleate, but again this may be due to normally low concentrations of the essential 18:2 fatty acid or to alternate metabolism. In this regard, when a diet rich in linoleate was fed to African Green monkeys, the amount of hepatic cholesteryl linoleate increased by 3.3-fold (35).…”
Section: Resultsmentioning
confidence: 98%